Establishing Sound - Altman, Rick (Cinémas)

(untitled) (Cinémas, 2013)
The history of film sound has usually been configured as a series of technological upheavals. In every case, the story has been told through technological innovations, as if changes in technology were alone responsible for the development of new sound strategies. The approach offered here differs markedly from these previous treatments of sound. Instead of concentrating on technological shifts, this article stresses technical decisions made by the soundmen and directors responsible for developing Hollywood’s standard approach to sound. Through succinct analysis of two key films, The First Auto (Warner, 1927) and It Happened One Night (Columbia, 1934), along with briefer treatment of The Big Trail (Fox, 1930), a distinction is made between “shot-by-shot” treatment of sound and “scene-by-scene” treatment of sound. The systematic use of sound in It Happened One Night to establish and maintain a coherent sense of place gives rise to recognition of the increasingly common use of what the article terms “establishing sound.” Parallel to Hollywood’s familiar technique of introducing each scene with an “establishing shot,” the use of establishing sound offers filmmakers an additional method of locating auditors and maintaining their relationship to the film.